The 40 cm Monitoring Telescope of the Universitätssternwarte Bochum. Issue 10 (December 2013) - Ramolla, M.; Drass, H.; Lemke, R.; Westhues, C.; Pozo Nuñez, F.; Barr Dominguez, A.; Haas, M.; Chini, R.; Murphy, M.
Abstract The new 40cm Bochum Monitoring Telescope (BMT) has started routine operation at the Universitätssternwarte Bochum (USB), located near Cerro Armazones in Chile. It has a 41′ × 27′ field of view (FoV) and is equipped with B and V broad band filters and three narrow band filters at 670, 680, and 690 nm. This makes the BMT ideally suited to perform photometric reverberation mapping of the Hα emission line of active galactic nuclei, where the line is redshifted into the narrow bands, and to monitor bright stars which would be saturated with large telescopes. As a complement to our Robotic Bochum Twin Telescope (RoBoTT) with 2°.7 FoV and 14 filters, the BMT is an efficient instrument to accurately study the variability of individual sources, provided that its smaller FoV covers a sufficient number of suitable comparison stars. Here we describe the telescope and its fully robotic operation, and present science verification data demonstrating the performance of the BMT. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)